ACTIVATION OF OLDER PEOPLE WITH THE USE OF OCCUPATIONAL THERAPY - Kaniewska-Mackiewicz, Ewa (The Modern Higher Education Review, 2021)
Over recent years, the number of people in late adulthood in Polish society has significantly increased, thereby there has appeared a strong need to focus on the quality of life of these people, on the offer of personal development, self-fulfilment in late adulthood, finding new horizons of interests, interesting forms of spending free time, but also the formation of places and services that provide support, care, assistance in daily activities, places of rehabilitation in the bio-psycho-social sphere. This paper describes the need of expanding services for the elderly based on occupational therapy. It also indicates what this type of activity consists of, what methods and techniques the therapist uses, and what benefits come from occupational therapy for the entire family of an elderly person.